The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12298-015-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

Mining expressed sequence tags of rapeseed (Brassica napus L.) to predict the drought responsive regulatory network

Abstract: It is of great significance to understand the regulatory mechanisms by which plants deal with drought stress. Two EST libraries derived from rapeseed (Brassica napus) leaves in non-stressed and drought stress conditions were analyzed in order to obtain the transcriptomic landscape of drought-exposed B. napus plants, and also to identify and characterize significant drought responsive regulatory genes and microRNAs. The functional ontology analysis revealed a substantial shift in the B. napus transcriptome to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…The only study in canola to date identified five drought‐induced microRNAs and one drought‐repressed microRNA, with six transcription factors and a kinase as predicted targets (Shamloo‐Dashtpagerdi et al ., ). These predicted targets are involved in ABA biosynthesis, BR and auxin signaling, and transcription (Shamloo‐Dashtpagerdi et al ., ). Results from this study, together with conserved drought‐responsive microRNAs discovered in other species, form an initial inventory of microRNA candidates that could potentially be manipulated to improve drought tolerance in canola.…”
Section: Translational Biology: Iterating Between a Thaliana And B mentioning
confidence: 97%
See 3 more Smart Citations
“…The only study in canola to date identified five drought‐induced microRNAs and one drought‐repressed microRNA, with six transcription factors and a kinase as predicted targets (Shamloo‐Dashtpagerdi et al ., ). These predicted targets are involved in ABA biosynthesis, BR and auxin signaling, and transcription (Shamloo‐Dashtpagerdi et al ., ). Results from this study, together with conserved drought‐responsive microRNAs discovered in other species, form an initial inventory of microRNA candidates that could potentially be manipulated to improve drought tolerance in canola.…”
Section: Translational Biology: Iterating Between a Thaliana And B mentioning
confidence: 97%
“…A recent study investigated drought‐responsive genes in B. juncea seedlings and observed that 132 transcription factors (40 induced and 92 repressed) and 452 kinases (42 induced and 410 repressed) were regulated by drought (Bhardwaj et al ., ). A similar observation was reported in an analysis of ESTs of B. napus under drought treatment (Shamloo‐Dashtpagerdi et al ., ). This study found that 17 transcription factors, eight protein kinases, and one protein phosphatase were drought‐regulated, including homologs of Arabidopsis protein phosphatase 2C ABI1 and the ABA biosynthesis gene ABA1 .…”
Section: Systems Biology Of Brassica Under Drought Stressmentioning
confidence: 97%
See 2 more Smart Citations
“…This issue rises from the fact that stress response in plants is an extremely complicated process (Pessarakli 2011). Multiplicity of the gene families and the complex interactions between TFs and cis-elements on the promoters of target genes as well as cross-talk between TFs in response to stress indicate the complexity of signaling networks involved in plant stress responses (Seki et al 2003;Shamloo-Dashtpagerdi et al 2015;Tuberosa and Salvi 2006). Therefore, assigning the relations among TFs in response to drought stress will uncover the actual function of them facilitating improvement of drought tolerant crops.…”
Section: Introductionmentioning
confidence: 99%